1993
DOI: 10.1101/gad.7.5.904
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tobacco mosaic virus cell-to-cell movement protein by a developmentally regulated plant cell wall-associated protein kinase.

Abstract: In host plants, cell-to-cell spread of tobacco mosaic virus (TMV) presumably occurs through intercellular connections, the plasmodesmata. TMV movement is mediated by a specific virus-encoded single-strand nucleic acid-binding protein, P30. The mechanism by which P30 operates is largely unknown. Here, we demonstrate that P30 expressed in transgenic plants is a phosphoprotein. We have developed an assay for in vitro phosphorylation of purified P30 by plant cell wall fractions and have localized the phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 39 publications
(43 reference statements)
5
116
2
1
Order By: Relevance
“…Coat proteins (CPs) of the Cauliflower mosaic virus (Martinez-Izquierdo and Hohn, 1987) and potyviruses (Ivanov et al, 2001;Fernández-Fernández et al, 2002) as well as movement protein (MP) of Tobacco mosaic virus (Atkins et al, 1991;Watanabe et al, 1992;Citovsky et al, 1993;Waigmann et al, 2000) are phosphorylated, and several functions of these proteins are affected by phosphorylation (Karpova et al, 1999;Kawakami et al, 1999;Waigmann et al, 2000). Previous studies also identified a PERK-Like Receptor Kinase, NsAK, that may regulate nuclear shuttle protein function through phosphorylation (Florentino et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Coat proteins (CPs) of the Cauliflower mosaic virus (Martinez-Izquierdo and Hohn, 1987) and potyviruses (Ivanov et al, 2001;Fernández-Fernández et al, 2002) as well as movement protein (MP) of Tobacco mosaic virus (Atkins et al, 1991;Watanabe et al, 1992;Citovsky et al, 1993;Waigmann et al, 2000) are phosphorylated, and several functions of these proteins are affected by phosphorylation (Karpova et al, 1999;Kawakami et al, 1999;Waigmann et al, 2000). Previous studies also identified a PERK-Like Receptor Kinase, NsAK, that may regulate nuclear shuttle protein function through phosphorylation (Florentino et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If this is also true for the ORF2 products of potexviruses, the apparent abundance of these proteins in inclusions in infected tissue would be more reasonable. However, it may also be possible that the EDCBs we observed, as well as those for PVX and FMV, are repositories for excess amounts of ORF2 products in infected plants, as suggested by Citovsky et al (1993). Therefore, the location of 28 kDa protein does not necessarily reflect the area in which it has a function.…”
mentioning
confidence: 79%
“…Young leaves of N. benthamiana or N. tabacum were infected mechanically with TMV (10 mg ml 21 ) or agroinjected with MP expression vector (Tyulkina et al, 2006). At different times post-inoculation (from 1 to 5 days), the leaves were treated as described by Citovsky et al (1993) with slight modifications. All operations were carried out at 4 uC.…”
Section: Methodsmentioning
confidence: 99%
“…Non-phosphorylatable mutants (del 43, sb3A) were movement-competent in N. tabacum and N. benthamiana Trutnyeva et al, 2005). Therefore, C-terminal phosphorylation was suggested to represent a host-dependent regulatory mechanism for inactivating the MP gating function in order to minimize detrimental effects of MP on host metabolism (Citovsky et al, 1993;Waigmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation